Extra-Axial Cystic Meningioma without Dural Attachment in an Adult: Case Report and Review of Literature - Diyora, Batuk; Kukreja, Sanjay; Dhal, Gagan; Devani, Kavin; Patel, Mehool; Wankhede, Ravi (Asian Journal of Neurosurgery, 2022)
Intraparenchymal meningiomas, meningiomas without dural attachment, and cystic meningioma are atypical and extremely rare, especially in adults. Only four cases of intraparenchymal cystic meningioma without dural attachment have been reported. A 47-year-old female presented with an altered sensorium. She had a progressive bifrontal headache for 2 months. Computed tomography scan of the brain showed an 8 cm × 6 cm cystic lesion with a solid component in the left frontoparietal region with a midline shift. The solid part of the lesion was enhancing on contrast but the cyst rim was not. Intraoperatively, the cyst was filled with amber-colored fluid, which was drained, and the solid component was completely excised. Histopathological examination of the solid tumor component confirmed cystic meningioma. At 2 years of follow-up, she has no evidence of recurrence. We report the fifth case of this very rare entity and review the literature.
Keywords: cyst; tumor; meningioma; intraparenchymal; deep sylvian fissure; dural attachment